2013
DOI: 10.25011/cim.v36i6.20628
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum YKL-40 levels with the presence and severity of coronary artery disease in patients with obstructive sleep apnea syndrome

Abstract: Purpose: Current evidence supports a robust association between obstructive sleep apnea syndrome (OSAS) and the risk of coronary artery disease (CAD). YKL-40, a 40 kDa heparin- and chitin-binding glycoprotein, is found to be associated with the presence of CAD. This study aims to examine the association of serum levels of YKL-40 with the presence and severity of CAD in patients with OSAS. Methods: A total of 246 patients with OSAS who underwent coronary angiography for the evaluation of CAD (134 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In addition, the results from recent studies on human subjects have suggested that chitinase-3-like protein 1 (Chi3l1), also termed YKL-40, might serve as a potential biomarker in the blood plasma and cerebrospinal fluid for AD diagnosis 24 - 29 . Furthermore, recent studies have reported that the expression level of Chi3l1 is increased in atherosclerotic aorta 30 , 31 and have demonstrated that increased plasma Chi3l1 is associated with endothelial dysfunction 32 , 33 and thromboembolic stroke 34 and have suggested Chi3l1 as a diagnostic marker for cardiovascular diseases 35 - 37 , whereas knockdown of Chi3l1 in ApoE -/- mice suppresses atherosclerotic plaque progression 30 and abdominal aortic aneurysm (AAA) development 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the results from recent studies on human subjects have suggested that chitinase-3-like protein 1 (Chi3l1), also termed YKL-40, might serve as a potential biomarker in the blood plasma and cerebrospinal fluid for AD diagnosis 24 - 29 . Furthermore, recent studies have reported that the expression level of Chi3l1 is increased in atherosclerotic aorta 30 , 31 and have demonstrated that increased plasma Chi3l1 is associated with endothelial dysfunction 32 , 33 and thromboembolic stroke 34 and have suggested Chi3l1 as a diagnostic marker for cardiovascular diseases 35 - 37 , whereas knockdown of Chi3l1 in ApoE -/- mice suppresses atherosclerotic plaque progression 30 and abdominal aortic aneurysm (AAA) development 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that YKL-40 is expressed by monocytes/macrophages in peripheral blood and synovial tissue [27][28][29][30][31]. Although the exact physiological function of YKL-40 is unknown, the results of clinical studies in community-acquired pneumonia, active rheumatoid arthritis, hepatic fibrosis, breast cancer, colorectal cancer, and human glioma have disclosed that serum levels of YKL-40 are correlated with the severity of disease [5][6][7][8][9][10][11][12][13]. Moreover, high levels of YKL-40 in serum and cerebrospinal fluid independently predict death in patients with pneumococcal bacteremia and purulent meningitis, respectively [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between the severity of the disease state and the levels of YKL-40 in either cerebrospinal fluid or sera of patients with a variety of pathological conditions has been demonstrated in the recent clinical studies, and most have speculated that YKL-40 might be a valuable biochemical marker of inflammation, similar to C-reactive protein [5][6][7][8][9][10][11][12][13][14][15]. YKL-40 can also be expressed in astrocytes and may take part in acute neuroinflammation [16][17][18].…”
Section: Introductionmentioning
confidence: 93%
“…20 This suggests that serum YKL-40 levels could also be utilized to predict the development of CAD in OSAS patients.…”
Section: Sciencementioning
confidence: 99%